Incorporating a Smartphone Video in a Theatrical Activity to Promote an Authentic Language Learning Environment in a Lower Secondary School Classroom - Yanti, Prima Gusti; Mulyono, Herri (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Theatrical activities have been used to promote an authentic learning environment. However, the incorporation of simple daily technology, like smartphones, to enable students to produce a video of their theatrical activities has not been explored in the Indonesian language learning classroom. This paper documents a video project conducted by lower secondary school students at a private school in Jakarta, Indonesia to examine whether a video project task could help create an authentic learning environment in a language classroom setting. Although the benefits of theatrical activities to promote authenticity in students’ learning experiences are evident in the literature, only a few students have access to such benefits. Many students were reluctant to get involved in the theatrical activities prepared by the teachers and only one cohort of students successfully completed the advertisement video assignment. Teachers’ instructional issues as well as students’ motivation and commitment to work collaboratively were identified as the barriers to produce the video.